Minimal supersolutions of BSDEs with lower semicontinuous generations - Gregor Heyne; Michael Kupper; Christoph Mainberger (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
We study the existence and uniqueness of minimal supersolutions of backward stochastic differential equations with generators that are jointly lower semicontinuous, bounded below by an affine function of the control variable and satisfy a specific normalization property.
Keywords: C61; C65; G11; 330; supersolutions of backward stochastic differential equations; semimartingale convergence; nonlinear expectations; Analysis; Stochastischer Prozess; Theorie